2019
DOI: 10.15407/spqeo22.01.111
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of cattle leucosis by using an biosensor based on surface plasmon resonance phenomenon

Abstract: The virus of cattle enzootic leucosis leads to high losses in rural economy, implies forced slaughter of sick animals, loss of the breed, decrease in productivity, violation of reproduction processes in industrial breeding and livestock sector. Among cattle infection diseases, leucosis takes the leading position and comprises 57% of all the other nosological forms, if taking into account severity of injuries in organs, large-scale character of these diseases and economic aftermath. This disease can be transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…An alternative method to ELISA and PCR for diagnosing bovine leukemia based on the SPR phenomenon was proposed in [27]. This study demonstrated for the first time that the SPR method enables detection of the antibodies to bovine leukemia virus in diluted solutions (1 vol.%) of slightly positive blood serum taken from diseased animals.…”
Section: Circular Economy and Climate Randimentioning
confidence: 95%
See 1 more Smart Citation
“…An alternative method to ELISA and PCR for diagnosing bovine leukemia based on the SPR phenomenon was proposed in [27]. This study demonstrated for the first time that the SPR method enables detection of the antibodies to bovine leukemia virus in diluted solutions (1 vol.%) of slightly positive blood serum taken from diseased animals.…”
Section: Circular Economy and Climate Randimentioning
confidence: 95%
“…This area is the closest to SPQEO and includes photonics technologies, electric battery technologies, quantum technologies, and microelectronics. We have already mentioned sensors for medical monitoring, environmental protection, converting sunlight into electricity, and more [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. As an example, quantum technologies are presented in [28].…”
Section: Technologymentioning
confidence: 99%
“…Our strategy for the next decade included theoretical consideration of new effects in low-dimensional semiconductor structures [7][8][9][10], establishment of new principles and approaches to create and study functionality of lasers and LEDS [11][12][13][14][15][16][17][18], clarification of some peculiarities in new hetero-and hybrid structures [19][20][21], application of sensor and photovoltaic cells [22][23][24][25][26][27], use of semiconductor, optic and quantum electronic devices in ecology, communications, renewable energetics and health care [28][29][30][31][32][33][34][35][36][37].…”
mentioning
confidence: 99%